Approach avoidance training in the eating domain: Testing the effectiveness across three single session studies. (1st February 2015) - Becker, Daniela; Jostmann, Nils B.; Wiers, Reinout W.; Holland, Rob W.
Highlights: We conducted three studies on the approach avoidance training in the eating domain. Overall, training did not consistently affect food preferences and behavior. Future research should incorporate different samples/more sessions. Our work highlights the complexity of (changing) eating behavior. Abstract: Dual-process models propose that impulsive behavior plays a key role in the development and maintenance of maladaptive eating patterns. Research outside the eating domain suggests that approach avoidance training, a paradigm which aims to modify automatic behavioral dispositions toward critical stimuli, is an effective tool to weaken unhealthy impulses. The present research tested the effectiveness of approach avoidance training in the eating domain. We conducted three single session studies with varying methodologies in a normal-weight female student population (total N  = 258), in which one group was always trained to avoid pictures of unhealthy food and to approach pictures of healthy food or neutral objects. We found no conclusive evidence that approach avoidance training can change participants' implicit and explicit food preferences and eating behavior. We discuss the potential and the limitations of approach avoidance training in the eating domain and provide suggestions for future research avenues.